Bibliography on English-speaking Quebec - O'Donnell, Brendan (2009)
This bibliography aims to help anyone studying English-speaking Quebec find material about the nature, history, contributions, and concerns of this diverse official language minority community. It reveals the wealth of available material and catalogues it in a useful way in the hope of stimulating further research on English-speaking Quebec. The bibliography contains secondary sources related to the study of English-speaking Quebec. It covers the period from the Conquest to the present day. Types of resources include everything from scholarly studies to magazine articles, by way of films and websites. Despite this, the bibliography does not claim to be exhaustive and excludes documents such as encyclopedia articles and entries in the Dictionary of Canadian Biography.... Website description

Working People Built BC - BC Labour Heritage Centre (Working People Built BC, 2004)
The BC Labour Heritage Centre Society was founded in 2004 with JJ (Jack) Munro as Chair. The Society preserves, documents and presents the rich history of working people in British Columbia. The Society engages in partnerships and projects that help define and express the role that work and workers have played in the evolution of social policy and its impact on the present and future shaping of the province. –Website "About" page.

Gender & Work Database - York University. Department of Politics; Vosko, Leah F. (2004)
The Gender & Work Database (GWD) is an online research tool designed for both researchers and students with varying levels of expertise. The database is informed by a feminist political economy approach and provides resources that facilitate research on gender and work. The GWD can be used as an interactive classroom tool, to obtain basic information on a topic, or as a research tool to examine complex social relations. ...[Following the introduction to the database,] there are six integrated and interactive modules that represent entry points into the study of gender and work, namely precarious employment, health care, unions, migration, unpaid work, and technology. –Website description
https://www.sshrc-crsh.gc.ca/results-resultats/prizes-prix/2019/insight_vosko-eng.aspx

Labor: Studies in Working-Class History - Labor and Working-Class History Associaiton (Labor: Studies in Working-Class History, 2003)
This journal is the official journal for the Labor and Working-Class History Association. The labor question—who will do the work and under what economic and political terms?—beckons today with renewed global urgency. As a site for both historical research and commentary, Labor hopes to provide scaffolding for understanding the roots of our current dilemmas. Although the tradition from which the journal derives its energy has focused primarily on social movements and institutions based on industrial labor, Labor intends to give equal attention to other labor systems and social contexts (agricultural work, slavery, unpaid and domestic labor, informal sector, the professions, etc.). Its focus begins on the US experience but extends to developments across the “American” hemisphere and to other transnational comparisons that shed light on the American experience.

The Work and Lifelong Learning Research Network - Ontario Institute for Studies in Education. Centre for the Study of Education and Work (2002)
Welcome to the website of the research network for: The Changing Nature of Work and Lifelong Learning in the New Economy: National and Case Study Perspectives. A grant awarded by the Social Sciences and Humanities Research Council of Canada (SSHRC), complementing work begun by the NALL (New Approaches to Lifelong Learning) research network, WALL is a part of the Initiative for the New Economy (INE), which aims to help Canadians understand and benefit from the ways in which the global economy is being transformed. Our network of investigators is composed of researchers from seven universities and more than 10 co-investigators from community groups and professional institutions across Canada. Benefiting from the contributions of international advisors, the WALL research network endeavours to identify gaps in workplace training and education in Canada and bring visibility to current learning and work issues and trends. –Website description

Just Labour: A Canadian Journal of Work and Society - York University. Centre for Research on Work and Society (2002)
Open access publication from 2002 to 2014 of York University's Centre for Research on Work and Society. Its mission, as stated in its inaugural issue, was as follows: "Just Labour explores the complex ways new technologies, subcontracting, new management strategies, and emerging self-employment are undermining the traditional employee-employer relationships and disciplining workers. Just Labour investigates how union action has been subverted by the international integration of capital, the proliferation of precarious employment, the challenges of organizing marginalized workers, and the increasingly anti-union practices of employers and the state. Just Labour addresses the culture and activities of Canadian workers and their unions as they face new challenges. The journal will explore new ideas and seek out fresh approaches to solving problems. Just Labour brings the work of leading academics and trade union researchers to a broad readership in popular, accessible language."